Association of Demographic Variables and Stress Level in Grandparents Rearing Grandchildren of Employed Parents (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: The responsibility of grandparents caring for their grandchildren comes with stress to the grandparents that can have an impact on their emotional health and psychological well-being. The aim of the study was designed to assess the level of stress and associated factors among grandparents raising their grandchildren of employed parents at selected area of Bangalore.MATERIALS AND METHODS: A cross-sectional descriptive research design and non-probability purposive sampling technique was used was used among 100 grandparents rearing their grandchildren at selected area of Bangalore. Modified parental stress scale (Berry and Jones 1995) was used to collect data from subjects. Descriptive, inferential statistics and chi-square was used to observe the association. P-value